PENGARUH FAKTOR PRIBADI TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN HANDPHONE SAMSUNG DI KOTA PALU - RAZANA, RAZANA (Fakultas Ekonomi Universitas Tadulako, 2015)
The purpose of this study is to determine the influence of personal factors on customer satisfaction in using Samsung mobile phone in Palu City. The variables studied are age and stage of life cycle (X1), job (X2), economic circumstances (X3), lifestyle (X4), personality and self-concept (X5), as well as customer satisfaction (Y). Research method is descriptive causal with sample of 60 respondents who selected by accidental side method. Data is analyzed with multiple linear regressions in SPSS software 19. Based on the analysis, the results confirmed that age and stage of life cycle (X1), job (X2), economic circumstances (X3), lifestyle (X4), personality and self-concept (X5), simultaneously and partially have significant influence on customer satisfaction in using Samsung mobile phone in Palu City.